Interdyscyplinarność w badaniach procesu rozumienia tekstu - Kusiak, Monika (Neofilolog, 2010)
The paper addresses the emergence of interdisciplinarity in humanities research. In the first section, it looks at various conceptions of interdisciplinarity. Then, it discusses an interdisciplinary nature of reading research, overviewing the concept of reading as explored by different fields of science. Finally, as an example of an interdisciplinary study into reading comprehension, the study conducted by the author of the paper is presented. The process of planning and the initial stages of conducting the study are discussed, along with the advantages of drawing on several disciplines in the study.